Cesium‐Vapor‐Based Delay of Single Photons Emitted by Deterministically Fabricated Quantum Dot Microlenses. Issue 2 (12th September 2019) - Bremer, Lucas; Fischbach, Sarah; Park, Suk‐In; Rodt, Sven; Song, Jin‐Dong; Heindel, Tobias; Reitzenstein, Stephan
Abstract: Quantum light sources are key building blocks of photonic quantum technologies. For many applications, it is of interest to control the arrival time of single photons emitted by such quantum devices, or even to store single photons in quantum memories. In situ electron beam lithography is applied to realize InGaAs quantum dot (QD)‐based single‐photon sources, which are interfaced with cesium (Cs) vapor to control the time delay of emitted photons. Via numerical simulations of the light–matter interaction in realistic QD‐Cs‐vapor configurations, the influence of the vapor temperature and spectral QD‐atom detuning is explored to maximize the achievable delay in experimental studies. As a result, this hybrid quantum system allows to trigger the emission of single photons with a linewidth as low as 1.54 GHz even under non‐resonant optical excitation and to delay the emission pulses by up to (15.71 ± 0.01) ns for an effective cell length of 150 mm. This work can pave the way for scalable quantum systems relying on a well‐controlled delay of single photons on a time scale of up to a few tens of nanoseconds. Abstract : Controlling the arrival time of individual photons is a key requirement for many applications in advanced quantum technology. Using an on‐demand non‐classical light source based on a deterministically fabricated quantum dot microlens, it is shown that light–matter interaction in dilute cesium vapor can lead to well‐controlled single‐photon delays up to 16 ns.